The effect of crushed ice ingestion on endurance performance and decision-making in hot and humid conditions - Saldaris, J. M.; Landers, G. J.; Lay, B. S. (International Journal of Performance Analysis in Sport, 2019)
This study examined endurance performance and choice reaction time (CRT) in the heat following precooling via crushed ice ingestion. Prior to an 800 kJ cycle time trial (CTT) in hot and humid conditions (34.2 ± 0.9°C, 52.9 ± 8.1% Relative Humidity), nine male endurance athletes consumed either 7 g·kg-1 of water (CON) or crushed ice (ICE) in 30 min. A 4-CRT task was completed before, during and post the CTT. Core temperature (Tcore) was significantly lower after precooling with ICE (-0.6 ± 0.4°C, p = 0.002) but not CON (-0.2 ± 0.2°C; p = 0.083). Mean power output improved by 7.8% following ICE compared to CON (p = 0.011). Throughout the CTT, CRT significantly improved in both conditions (p = 0.036), and although no significant differences occurred between conditions (p = 0.421), a moderate effect at 800 kJ suggests that ICE was becoming faster (d = 0.56, 0.25-1.32 90% CI). Thermal sensation was lower with ICE (p = 0.05); however, heart rate and perceived exertion were similar between conditions (p > 0.05). Ice ingestion significantly reduced Tcore coinciding with improved CTT performance. However, it remains equivocal whether ice ingestion is beneficial for decision-making during exercise in the heat.